Effects of Bunch Rot (Botrytis cinerea) and Powdery Mildew (Erysiphe necator) Fungal Diseases on Wine Aroma - Lopez Pinar, Angela; Rauhut, Doris; Ruehl, Ernst; Buettner, Andrea (Frontiers in Chemistry, 2017)
This study aimed to characterize the effects of bunch rot and powdery mildew on the primary quality parameter of wine, the aroma. The influence of these fungal diseases was studied by comparative Aroma Extract Dilution Analyses (AEDA) and sensory tests. The effect of bunch rot was investigated on three grape varieties, namely White Riesling, Red Riesling and Gewürztraminer and that of powdery mildew on the hybrid Gm 8622-3; thereby, samples were selected that showed pronounced cases of infection to elaborate potential currently unknown effects. Both infections revealed aromatic differences induced by these fungi. The sensory changes were not associated with one specific compound only, but were due to quantitative variations of diverse substances. Bunch rot predominantly induced an increase in the intensities of peach-like/fruity, floral and liquor-like/toasty aroma notes. These effects were found to be related to variations in aroma substance composition as monitored via AEDA, mainly an increase in the FD factors of lactones and a general moderate increase of esters and alcohols. On the other hand, powdery mildew decreased the vanilla-like character of the wine while the remaining sensory attributes were rather unaffected. Correspondingly, FD factors of the main aroma constituents were either the same or only slightly modified by this disease. Moreover, bunch rot influenced the aroma profiles of the three varieties studied to a different degree. In hedonic evaluation, bunch rot-affected samples were rated as being more pleasant in comparison to their healthy controls in all three varieties while the powdery mildew-affected sample was rated as being less pleasant than its healthy control.